2014
DOI: 10.2174/1381612820666140128215756
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Inhibits Cell Growth and Invasion Through Regulation of miR-27a in Pancreatic Cancer Cells

Abstract: Our findings demonstrated that genistein plays a tumor suppressor role in part through inhibition of miR-27a in pancreatic cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…In the current study, genistein activated miR-27a expression of NSCLC. Xia et al (22) demonstrated that genistein inhibits cell growth of pancreatic cancer cells through regulation of miR-27a and human uveal melanoma cells (23). …”
Section: Discussionmentioning
confidence: 99%
“…In the current study, genistein activated miR-27a expression of NSCLC. Xia et al (22) demonstrated that genistein inhibits cell growth of pancreatic cancer cells through regulation of miR-27a and human uveal melanoma cells (23). …”
Section: Discussionmentioning
confidence: 99%
“…IFs act as phytoestrogens and prevent tumorigenesis in rodent models via various bioactivities. IFs have been previously demonstrated to target all major epigenetic mechanisms regulating gene expression in in vitro and in vivo studies (36)(37)(38)(39)(40)(41)(42)(43). Greathouse et al (44) have recently reported that genistein-mediated phosphorylation of zeste homolog 2 was able to inhibit its activity and promote benign uterine cancers in Eker rats.…”
Section: Discussionmentioning
confidence: 99%
“…Qin et al, 2014) or effects of isoflavones on DNA methylation (W. Y. Qin et al, 2009) or microRNAs (Xia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%